To the collapse of the structures: the concerns in the Colonial and Republican period in the archaeological site of Campoy - Martínez Sulca, Winnie Celeste (2022)
The hispanic occupation in Lima caused a series of sociopolitical changes, which affected the configuration of the new landscape on the right bank of the Rímac middle valley. In the case of the archaeological site of the Huaca Fortaleza de Campoy, the results of the excavations carried out allow us to observe, in addition to evidence of pre-Hispanic occupation, a set of activities associated with the colonial and republican periods, which are complemented with data extracted of historical documents. Among the identified activities is the raising of cattle, which would have been part of a local tradition around the use of space since pre-Hispanic times. However, the development of this activity, during the Hispanic reoccupation brought as a consequence the adaptation and reconfiguration of the pre-Hispanic spaces of the site, such as the closure of enclosures and/or the opening of new accesses in order to shelter the new resources. The latter were part of the local production that supplied the city of Lima in an important way and that was still maintained until the end of the 19th century and the beginning of the 20th century.